User eXperience and Translatability Viewed through the Lens of a Triple Constraint: Time, Cost and Quality - Bowker, Lynne; Ciro, Jairo Buitrago (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2016)
User eXperience (UX) guidelines make web content engaging, while controlled language guidelines make it easily translatable. As organizations seek to serve diverse linguistic populations, the question of whether UX and translatability are compatible or in conflict becomes increasingly relevant, particularly when it comes to balancing time, cost and quality. This paper reports on a multilingual recipient evaluation of web content. Les lignes directrices venues de l’expérience utilisateur (UX) rendent les contenus Web invitants, tandis que les directives de langage ciblé les rendent facilement traduisibles. Du fait que les organisations cherchent à servir des populations linguistiques diverses, la question de savoir si l’expérience utilisateur et la traductibilité sont compatibles ou en conflit devient de plus en plus pertinente, en particulier quand il s’agit d’équilibrer temps, coût et qualité. Cet article présente une évaluation par un destinataire multilingue de contenus Web.